Vessel Enlargement in Development and Pathophysiology - Gifre-Renom, Laia; Jones, Elizabeth A. V. (Frontiers in Physiology, 2021)
Abstract From developmental stages until adulthood, the circulatory system remodels in response to changes in blood flow in order to maintain vascular homeostasis. Remodelling processes can be driven by de novo formation of vessels or angiogenesis, and by the restructuration of already existing vessels, such as vessel enlargement and regression. Notably, vessel enlargement can occur as fast as in few hours in response to changes in flow and pressure. The high plasticity and responsiveness of blood vessels rely on endothelial cells. Changes within the bloodstream, such as increasing shear stress in a narrowing vessel or lowering blood flow in redundant vessels, are sensed by endothelial cells and activate downstream signalling cascades, promoting behavioural changes in the involved cells. This way, endothelial cells can reorganize themselves to restore normal circulation levels within the vessel. However, the dysregulation of such processes can entail severe pathological circumstances with disturbances affecting diverse organs, such as human hereditary telangiectasias. There are different pathways through which endothelial cells react to promote vessel enlargement and mechanisms may differ depending on whether remodelling occurs in the adult or in developmental models. Understanding the molecular mechanisms involved in the fast-adapting processes governing vessel enlargement can open the door to a new set of therapeutical approaches to be applied in occlusive vascular diseases. Therefore, we have outlined here the latest advances in the study of vessel enlargement in physiology and pathology, with a special insight in the pathways involved in its regulation.